2022
DOI: 10.1200/jco.2022.40.16_suppl.2520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intratumoral INT230-6 on tumor necrosis and promotion of a systemic immune response: Results from a multicenter phase 1/2 study of solid tumors with and without pembrolizumab (PEM) [Intensity IT-01; Merck KEYNOTE-A10].

Abstract: 2520 Background: INT230-6 is a new product with a unique dual anti-cancer mechanism. The drug is comprised of cisplatin (CIS) and vinblastine (VIN) co-formulated with an amphiphilic molecule that enables drug dispersion throughout a tumor and passive diffusion into cancer cells following intratumoral (IT) delivery. A neoadjuvant study in breast cancer confirms that a single injection can kill 95% of an injected tumor and recruit TILs. Methods: INT230-6 treatments are Q2W for up to 5 treatments followed by mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Preclinical studies have demonstrated INT230-6's efficacy against large tumors and its ability to kill injected tumors and elicit a local T-cell-mediated immune response in animal models [43]. Completed in 2023, an abstract for a human phase I trial affirms INT230-6's rapid tumor killing and immune activation properties [89]. Safety and tolerability are also being assessed for ERAS-601, an oral allosteric SHP2 inhibitor, as a monotherapy or in combination with Cetuximab and Pembrolizumab [45].…”
Section: Cyclin-dependent Kinases (Cdk) Inhibitorsmentioning
confidence: 99%
“…Preclinical studies have demonstrated INT230-6's efficacy against large tumors and its ability to kill injected tumors and elicit a local T-cell-mediated immune response in animal models [43]. Completed in 2023, an abstract for a human phase I trial affirms INT230-6's rapid tumor killing and immune activation properties [89]. Safety and tolerability are also being assessed for ERAS-601, an oral allosteric SHP2 inhibitor, as a monotherapy or in combination with Cetuximab and Pembrolizumab [45].…”
Section: Cyclin-dependent Kinases (Cdk) Inhibitorsmentioning
confidence: 99%
“…A novel drug, INT230-6, made from a cell permeation enhancer and classical chemotherapeutics cisplatin and vinblastine, has been tested in a phase 1/2 trial (NCT03058289) [ 133 ]. A total of 5 patients with advanced or metastatic SCCs were included: only 1/5 was alive at the end of follow-up and he had been treated with intralesional INT230-6 (>50% tumor burden) and pembrolizumab [ 143 ]. INT230-6 is well tolerated as a monotherapy or in combination with pembrolizumab [ 143 ].…”
Section: Emerging Treatments and Future Directionsmentioning
confidence: 99%
“…A total of 5 patients with advanced or metastatic SCCs were included: only 1/5 was alive at the end of follow-up and he had been treated with intralesional INT230-6 (>50% tumor burden) and pembrolizumab [ 143 ]. INT230-6 is well tolerated as a monotherapy or in combination with pembrolizumab [ 143 ].…”
Section: Emerging Treatments and Future Directionsmentioning
confidence: 99%